Analysis of antigen receptor genes in Hodgkin's disease. Issue 4 (April 1993) - Angel, C A; Pringle, J H; Naylor, J; West, K P; Lauder, I
Abstract : AIM–To analyse the configuration of the antigen receptor genes in Hodgkin's disease. METHODS–DNA extracted from 45 samples of Hodgkin's disease was analysed using Southern blotting and DNA hybridisation, using probes to the joining region of the immunoglobulin heavy chain gene, the constant region of kappa immunoglobulin light chain gene, and the constant region of the beta chain of the T cell receptor gene. RESULTS–A single case of nodular sclerosing disease showed clonal rearrangement of the immunoglobulin heavy and light chain genes, all other samples having germline immunoglobulin genes. The nature of the clonal population in the diseased tissue is uncertain, because the intensity of the rearranged bands did not correlate with the percentage of Reed-Sternberg cells present. The T cell receptor genes were in germline configuration in all the samples. CONCLUSIONS–Antigen receptor gene rearrangement is a rare finding in unselected cases of Hodgkin's disease.